Pengaruh Insentif dan Budaya Kerja Terhadap Komitmen Karyawan Untuk Tetap Bekerja Pada PT Wana Sawit Subur Lestari 2 di Kabupaten Seruyan - Budi Utomo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The study aims to determine the effect of incentives and work culture of the employees commitment to keep working on sustainable luch PT Wana Sawit Subur Lestari 2 in Seruyan. With a sample of 81 people. Sampling using random sampling. This study uses quantitative methods using three variables incentives, work culture, and employee commitment to keep working. To analyze the data used regression and simple linier correlation test. Data collection techniques are questionnaire literature studies, field studies. Result of analyze showed that there are significant incentives variable, and the work culture of the employees’ commitment to keep working on sustainable luch PT Wana Sawit Subur Lestari 2 in distrik Seruyan. 34,3% of the variation that occurs on the employee’s commitment to keep working is influenced by incentives and work culture. While the remaining 65,7% is influenced by other factor